Discovery and development of exome‐based, co‐dominant single nucleotide polymorphism markers in hexaploid wheat (Triticum aestivum L.). Issue 3 (20th December 2012) - Allen, Alexandra M.; Barker, Gary L. A.; Wilkinson, Paul; Burridge, Amanda; Winfield, Mark; Coghill, Jane; Uauy, Cristobal; Griffiths, Simon; Jack, Peter; Berry, Simon; Werner, Peter; Melichar, James P. E.; et al.
Summary: Globally, wheat is the most widely grown crop and one of the three most important crops for human and livestock feed. However, the complex nature of the wheat genome has, until recently, resulted in a lack of single nucleotide polymorphism (SNP)‐based molecular markers of practical use to wheat breeders. Recently, large numbers of SNP‐based wheat markers have been made available via the use of next‐generation sequencing combined with a variety of genotyping platforms. However, many of these markers and platforms have difficulty distinguishing between heterozygote and homozygote individuals and are therefore of limited use to wheat breeders carrying out commercial‐scale breeding programmes. To identify exome‐based co‐dominant SNP‐based assays, which are capable of distinguishing between heterozygotes and homozygotes, we have used targeted re‐sequencing of the wheat exome to generate large amounts of genomic sequences from eight varieties. Using a bioinformatics approach, these sequences have been used to identify 95 266 putative single nucleotide polymorphisms, of which 10 251 were classified as being putatively co‐dominant. Validation of a subset of these putative co‐dominant markers confirmed that 96% were true polymorphisms and 65% were co‐dominant SNP assays. The new co‐dominant markers described here are capable of genotypic classification of a segregating locus in polyploid wheat and can be used on a variety of genotyping platforms; as such, they represent a powerful tool for wheat breeders. These markers and related information have been made publically available on an interactive web‐based database to facilitate their use on genotyping programmes worldwide.